Guarantees of individuals in federal regions against federal administrative authorities - Saeed, Hawraman Mohammed; Jalal, Yahya (Journal of Legal and Political Studies, 2025)
The federal administrative authorities possess exclusive powers as stipulated in the constitution. Among their duties is the issuance of regulations and decisions covering all parts of the state, as well as issuing instructions to implement laws that affect the rights and freedoms of individuals. However, does the power of the federal administrative authorities weaken the administrative authorities in the regions and confuse the rights of individuals? If the administrative authorities in the centre insist on making laws and enforcing their positions, what can the regional authorities do or appeal against their centre’s decisions? This research attempts to answer these questions and address the problems in two sections. The first section deals with the exclusive powers of the federal administrative authorities that affect the rights and legal standings of individuals, while the second section addresses the power of the regional authorities and, most importantly, the legal guarantees for the rights of individuals living in the regions. Keywords: Guarantees, Regions, Individuals, Federal Authorities
Keywords: Guarantees; Regions; Individuals; Federal Authorities